Building Green Supply Chain Collaboration at the Jurisdictional Level Towards Sustainable Palm Oil - Laurentius Vita Baskara; Wahyuningsih Santosa (Politeknik Siber Cerdika Internasional, 2025)
The palm oil industry plays an important role in meeting the world's vegetable oil needs, but faces sustainability challenges such as deforestation, land degradation, and land conflicts. This study analyzes the implementation of deforestation-free green supply chain practices in Kandis District, Siak Regency, Riau. Data were collected through in-depth interviews, field observations, and document analysis. The results show that companies have started to implement ISPO certification standards, including environmental impact management, and multi-stakeholder collaboration, having a significant impact in supporting the palm oil sustainability industry. However, in the implementation of green supply chains, challenges were found in the data collection of supply chains up to the farm level, due to the lack of trust of farmers and the absence of incentives, so it has not been able to ensure deforestation-free supply chains. The jurisdictional approach works to strengthen multi-stakeholder collaboration and accelerate the adoption of sustainable palm oil practices and green supply chains. The conclusion of this study confirms that the implementation of deforestation-free green supply chains can be achieved through the support of improved policies, governance, accelerated ISPO certification, farmer assistance and encouraging partnerships between companies and smallholders, in support of sustainable palm oil practices as a whole.